2020
DOI: 10.1038/s41467-020-17143-2
|View full text |Cite
|
Sign up to set email alerts
|

Orthophosphate increases the efficiency of slow muscle-myosin isoform in the presence of omecamtiv mecarbil

Abstract: Omecamtiv mecarbil (OM) is a putative positive inotropic tool for treatment of systolic heart dysfunction, based on the finding that in vivo it increases the ejection fraction and in vitro it prolongs the actin-bond life time of the cardiac and slow-skeletal muscle isoforms of myosin. OM action in situ, however, is still poorly understood as the enhanced Ca 2+-sensitivity of the myofilaments is at odds with the reduction of force and rate of force development observed at saturating Ca 2+. Here we show, by comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 66 publications
2
33
1
Order By: Relevance
“…OM was identified in a high-throughput screen designed to identify drugs that increase the rate of P I release from actomyosin-ADP-P i , with the goal of increasing the β-cardiac myosin duty ratio and heart contractility ( Malik et al, 2011 ). It was subsequently found that OM increases cardiac contractility by indirect activation of the muscle thin filament ( Woody et al, 2018b ; Governali et al, 2020 ). OM suppresses the working stroke of WT-myosin, similar to the effect of the R712L mutation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OM was identified in a high-throughput screen designed to identify drugs that increase the rate of P I release from actomyosin-ADP-P i , with the goal of increasing the β-cardiac myosin duty ratio and heart contractility ( Malik et al, 2011 ). It was subsequently found that OM increases cardiac contractility by indirect activation of the muscle thin filament ( Woody et al, 2018b ; Governali et al, 2020 ). OM suppresses the working stroke of WT-myosin, similar to the effect of the R712L mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Addition of OM to β-cardiac myosin stabilizes the pre-powerstroke state of WT-myosin ( Rohde et al, 2017 ), and we previously found that OM drastically reduced myosin’s working stroke for translocating actin and prolonged its actin attachment duration ( Woody et al, 2018b ). Although OM abrogates the working stroke of myosin, the prolonged attachment increases calcium sensitivity in muscle fibers via cooperative activation of the thin filament (TF) regulatory system, which activates the muscle ( Governali et al, 2020 ). At submicromolar concentrations, it has been shown to improve cardiac output in both animal models and in human clinical trials ( Malik et al, 2011 ; Teerlink et al, 2016 ; Cleland et al, 2011 ; Teerlink, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…These molecules can also be used as tools to understand the molecular mechanisms that govern contraction and relaxation. Some myosin activators, such as Omecamptiv Mercarbil, alter the dynamics of the actin-myosin cross-bridge cycle (Woody et al 2018;Governali et al 2020). However, augmentation of contraction may come at the cost of altered or impaired relaxation, a critical aspect of muscle function that depends on the rate of actin-myosin cross-bridge detachment (Janssen, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…2018; Governali et al . 2020). However, augmentation of contraction may come at the cost of altered or impaired relaxation, a critical aspect of muscle function that depends on the rate of actin–myosin cross‐bridge detachment (Janssen, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although OM abrogates the working stroke of myosin, the prolonged attachment increases calcium sensitivity in muscle fibers via cooperative activation of the thin filament regulatory system, which activates the muscle [14]. At submicromolar concentrations, it has been shown to improve cardiac output in both animal models and in human clinical trials [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%